2022
DOI: 10.3389/fimmu.2022.964365
|View full text |Cite
|
Sign up to set email alerts
|

Circulating interleukin-38 concentrations in healthy adults

Abstract: Interleukin (IL)-38 is the latest discovered member of the interleukin-1 family, which has anti-inflammatory properties similar to IL-36Ra. Several studies compared circulating IL-38 concentrations in healthy and diseased populations to characterize its role in both auto-immune and inflammatory pathologies, with both higher and lower concentrations being associated with certain diseases. However, in order to use IL-38 as a biomarker, a reference range in healthy adults is needed. To establish a reference IL-38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…However, we recently demonstrated that the blood collection method does not influence the IL-38 concentrations detected by enzyme-linked immunosorbent assay (ELISA). 55 We further observed a positive correlation between Ddimer and IL-38 in men of the validation cohort. Elevated D-dimer is a prognostic marker for severe COVID-19, 56 as well as for thrombotic complications, and is associated with increased proinflammatory cytokine levels such as IL-6.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…However, we recently demonstrated that the blood collection method does not influence the IL-38 concentrations detected by enzyme-linked immunosorbent assay (ELISA). 55 We further observed a positive correlation between Ddimer and IL-38 in men of the validation cohort. Elevated D-dimer is a prognostic marker for severe COVID-19, 56 as well as for thrombotic complications, and is associated with increased proinflammatory cytokine levels such as IL-6.…”
Section: Discussionsupporting
confidence: 56%
“…A potential confounder for the detection of IL‐38 may be due to differences between plasma and serum. However, we recently demonstrated that the blood collection method does not influence the IL‐38 concentrations detected by enzyme‐linked immunosorbent assay (ELISA) 55 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyzing IL-38 and rs6743376 in the context Rheumatoid Arthritis (RA) is crucial for several reasons (Teufel et al, 2022). Firstly, understanding IL-38's role offers potential therapeutic avenues by regulating inflammatory responses in RA.…”
Section: Introductionmentioning
confidence: 99%